Analysis of the Application of Just in Time and Total Productive Maintenance on Production Efficiency at CV XYZ - Nando, Fiky Two; Bintang Pamungkas, Mohammad Rafly Rafsyanjani; Kusuma, Febiola Alyza; Ramadan, Prananda Aditia; Sautra, Tri Wahyu; Saputra, Mohamad Risfi (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to evaluate the implementation of the Just-In-Time (JIT) and Total Productive Maintenance (TPM) methods as an effort to improve production process efficiency at CV XYZ, a metal manufacturing company located in East Java. The research approach was conducted through a case study utilizing primary data, including raw material requirements, ordering and storage costs, machine downtime duration, and product defect percentage. The analysis involved calculating the Economic Order Quantity (EOQ) and Reorder Point (ROP) to determine an optimal raw material procurement strategy, as well as measuring Overall Equipment Effectiveness (OEE) to assess machine performance before and after TPM implementation. Based on the analysis results, the application of JIT produced an EOQ value of 200 tons per order and an ROP value of 280 tons, which led to a reduction in total inventory costs from IDR 135,000,000 to IDR 108,000,000 per year, representing an efficiency improvement of approximately 20%. Meanwhile, TPM implementation increased the average OEE value from 78% to over 85%, accompanied by a decrease in machine downtime and product defect rates. The integration of JIT and TPM proved effective in creating a more consistent production system, reducing the need for safety stock, and improving process reliability and cost efficiency. Overall, the combined implementation of these two methods contributes significantly to enhancing operational efficiency and product quality, making it a potential model for other manufacturing companies in sustainable inventory management and machine maintenance practices.